Pig tongue soft robot mimicking intrinsic tongue muscle structure - Yuta Ishikawa; Hiroyuki Nabae; Megu Gunji; Gen Endo; Koichi Suzumori (Frontiers in Robotics and AI, 2025)
Animal muscles have complex, three-dimensional structures with fibers oriented in various directions. The tongue, in particular, features a highly intricate muscular system composed of four intrinsic muscles and several types of extrinsic muscles, enabling flexible and diverse movements essential for feeding, swallowing, and speech production. Replicating these structures could lead to the development of multifunctional manipulators and advanced platforms for studying muscle-motion relationships. In this study, we developed a pig tongue soft robot that focuses on replicating the intrinsic muscles using thin McKibben artificial muscles, silicone rubber, and gel. We began by performing three-dimensional scans and sectional observations in the coronal and sagittal planes to examine the arrangement and orientation of the intrinsic muscles in the actual pig tongue. Additionally, we used the diffusible iodine-based contrast-enhanced computed tomography (Dice-CT) technique to observe the three-dimensional flow of muscle pathways. Based on these observations, we constructed a three-dimensional model and molded the pig tongue shape with silicone rubber and gel, embedding artificial muscles into the robot body. We conducted experiments to assess both the motion of the tongue robot’s tip and its stiffness during muscle contractions. The results confirmed characteristic tongue motions, such as tip extension, flexion, and lateral bending, as well as stiffness changes during actuation, suggesting the potential for this soft robot to serve as a platform for academic and engineering studies.